AB0328 Rituximab in rheumatoid arthritis, a monocentric analysis of effectiveness. (23rd January 2014) - Madureira, P.; Vieira, R.; Terroso, G.; Aleixo, A.; Fonseca, R.; Gonçalves, D.; Pimenta, S.; Bernardo, A.; Bernardes, M.; Costa, L.
Abstract : Background: Rituximab in association with methotrexate (MTX) is approved for the treatment of severe rheumatoid arthritis (RA) after failure of at least 1 anti-tumour necrosis factor-α (anti-TNF). Its efficacy has been demonstrated in randomized control trials, but the daily clinician experience with this biologic therapy has only started to arise in the last few years. Objectives: To analyze the effectiveness of rituximab in RA patients, and the response differences between anti-TNF naïve patients and those previously exposed to anti-TNF. Methods: A retrospective analysis of all patients with RA receiving treatment with rituximab was done in a rheumatology department of a portuguese university hospital, selected from the national database for rheumatic patients. The demographic and clinic baseline data, disease activity at 3, 6 and 12 months of therapy (DAS28 and EULAR response) and HAQ at 12 months were collected. The variations in DAS28, HAQ and EULAR response were determined, as well as their difference according to previous anti-TNF exposure. The differences between patients under rituximab in monotherapy or under concomitant classic disease modifying anti-rheumatic drugs (DMARDs) were also determined. Results: In December 2012, 36 patients met the inclusion criteria; 94.4% were women, with median disease duration of 17.5 years. Rheumatoid factor and/or anti-cyclic citrullinated peptide (anti-CCP) were positive in 86.1% of patients. 50% of the patients were receiving methotrexate and 22.2% other DMARDs, while 27.8% were under rituximab in monotherapy. The median baseline DAS28 was 6.3 and median baseline HAQ was 2. There were no significant differences between anti-TNF naïve and the anti-TNF failure groups in terms of baseline characteristics, with the exception of the disease duration, significantly shorter in the anti-TNF naïve patients group (median of 11.5 and 21.5 respectively, p = 0.008). DAS28 variation at 3 months wasn't significant (p = 0.108), but at 6 months the median DAS28 had a significant reduction of 0.7 (p = 0.002) and at 12 months of 1.57 (p < 0.001). 69.6% of the patients achieved EULAR response (moderate or good) at 12 months. The anti-TNF naïve patients and those with previous anti-TNF failure did not differ significantly in terms of DAS28 at 3, 6 and 12 months (p = 0.064, p = 0.223 e p = 0.413, respectively), nor in EULAR response at 12 months (71.4% vs. 78.8%, p = 1). There were no significant differences in DAS28 at 3, 6 and 12 months (p = 0.560, p = 0.719 e p = 0.651, respectively) between the patients receiving rituximab in monotherapy and the ones with concomitant DMARDs. In the EULAR response there was no significant difference, with 62.5% of the monotherapy patients achieving an EULAR response against 73.3% of the patients under classic DMARDs (p = 0.657). Conclusions: This analysis demonstrates once again the efficacy of rituximab in RA treatment, and that its efficacy remains similar in patients with previous failure to anti-TNF, or when used in monotherapy. It also suggests that 3 months of follow-up is too soon to evaluate the efficacy of rituximab treatment. Disclosure of Interest: None Declared